1987
DOI: 10.1111/j.1365-2125.1987.tb03156.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐exercise hypotension: the effects of epanolol or atenolol on some hormonal and cardiovascular variables in hypertensive men.

Abstract: Tyne1 Eight men with primary hypertension were treated for 3 weeks with placebo, epanolol (200 mg or 400 mg), or atenolol 100 mg in a randomised cross-over study. Each active treatment period was preceded by a 3 week placebo treatment period and both investigators and subjects were blind to the active drug sequence. 2 At the end of each period, measurements were made of resting cardiovascular (heart rate, blood pressure, forearm blood flow) and biochemical variables (plasma renin, angiotensin II, aldosterone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
4

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 26 publications
(25 reference statements)
1
22
0
4
Order By: Relevance
“…[13][14][15] However, its occurrence in normotensive humans is inconsistent. Although we have found that PEH can be detected in normotensive individuals, 16 it was found to be much less consistent and of lesser magnitude than in hypertensive individuals.…”
Section: Does Peh Occur In All Individuals?mentioning
confidence: 99%
See 3 more Smart Citations
“…[13][14][15] However, its occurrence in normotensive humans is inconsistent. Although we have found that PEH can be detected in normotensive individuals, 16 it was found to be much less consistent and of lesser magnitude than in hypertensive individuals.…”
Section: Does Peh Occur In All Individuals?mentioning
confidence: 99%
“…10,11,19,22,24,[31][32][33]35,41,[43][44][45][59][60][61]63,71,72 Treadmill exercise at similar intensities has also been documented to elicit PEH. 14,15,20,25,34,40,[55][56][57][58] Direct comparisons of the effect of exercise intensity have, for the most part, found that PEH occurs independent of exercise intensity. We have found no difference in the magnitude of hypotension following 30 min of cycle ergometry at power outputs eliciting 50% and 75% V · O 2 Peak in normotensive volunteers.…”
Section: Intensity Of the Exercisementioning
confidence: 99%
See 2 more Smart Citations
“…Studies examining both peripherally [1][2][3] and centrally [4][5][6][7] mediated mechanisms have produced inconsistent results.…”
Section: Introductionmentioning
confidence: 99%